2002
DOI: 10.1136/bjo.86.12.1390
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver and intraobserver variability of measurements of uveal melanomas using standardised echography

Abstract: Aim: To report on the intraindividual and interindividual variability of tumour size (height and base diameter) measurements using standardised echography in a masked prospective study. Methods: 20 consecutive eyes of 20 patients were examined on four different visits by three experienced examiners using standardised echography. As common in standardised echography, tumour height was evaluated with A-scan technique, while transverse and longitudinal base diameter were calculated with B-scan. Results: Tumour he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Furthermore, we performed standardized A-scan echography to measure the maximum tumour height, as described by Ossoinig et al [22]. In previous studies we had identified tumour height measurements using A-scan (ultrasound B-scan-S V-plus, Memory Card Version S 2.07, all by Biovision/Schwind, Kleinostheim, Germany, now HaagStreit, Clermont-Ferrand, France) to be the most accurate echographic parameter obtainable [13]. The patients were referred to a tumour specialist to be screened for metastatic disease by liver ultrasound and liver enzyme tests (alkaline phosphatase, AST, ALT, bilirubin) as well as chest X-ray.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we performed standardized A-scan echography to measure the maximum tumour height, as described by Ossoinig et al [22]. In previous studies we had identified tumour height measurements using A-scan (ultrasound B-scan-S V-plus, Memory Card Version S 2.07, all by Biovision/Schwind, Kleinostheim, Germany, now HaagStreit, Clermont-Ferrand, France) to be the most accurate echographic parameter obtainable [13]. The patients were referred to a tumour specialist to be screened for metastatic disease by liver ultrasound and liver enzyme tests (alkaline phosphatase, AST, ALT, bilirubin) as well as chest X-ray.…”
Section: Methodsmentioning
confidence: 99%
“…In temporal lesions and peripheral tumors, US values differed more from CT/MRI values than in nasal or central tumors. This can be explained by an angular distortion of the US measurements when scanning cannot be done orthogonally to the sclera, which is not discussed by Haritoglou et al [4], where one-dimensional A-scan measurements are described as being more precise than 2-D B-scans.…”
Section: Discussionmentioning
confidence: 97%
“…CT and MRI can reproduce position information to an accuracy of ± 1-2 mm in neurosurgical stereotactic localization [9] and in stereotactic radiosurgery [15]. The interobserver variability of US has been described as 0.6 mm (2 SD [standard deviations]) [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary advantage of A-Scan ultrasonography when measuring the thickness of a choroidal tumor is the technique's ability to precisely identify the location of and distance between the anterior tumor margin and the sclera using quantitative spikes of echogenicity [29]. However, obtaining this information accurately is time-consuming and technically difficult.…”
Section: A-scanmentioning
confidence: 99%